(untitled) (Research, Society and Development, 2025)
Objective: This study aimed to understand the association between parafunctional habits of dentistry students in the city of Recife and academic life. Methodology: An observational, cross-sectional study was carried out through a questionnaire answered by dentistry students who were regularly enrolled in public or private colleges in the city of Recife. Data was collected through a structured questionnaire on Google Forms® platform and included in a Microsoft Excel® database spreadsheet. Data analysis was performed using descriptive statistics to analyze the frequency of associations with Chi-Square tests and Fisher’s Exact Test. Results: The sample consisted of 276 students with a mean age of 21.36 years, and it was observed that the majority were from private institutions. There was a statistically significant association between anatomical and physiological knowledge of the stomatognathic system and the abandonment of parafunctional habits (p<0.001). Of the students who reported having abandoned some of the habits, 70.7% (70) considered that anatomical and physiological knowledge contributed to the abandonment. Conclusion: It is concluded that dental students are great reflections of the current situation regarding the relationship between anxiety, stress and parafunctional habits, since more than half of the participants considered themselves stressed and anxious. In a large part of the sample, anatomical and physiological knowledge of the stomatognathic system did not contribute to the abandonment of parafunctional habits.